Recent advances and perspectives on constructing metal oxide semiconductor gas sensing materials for efficient formaldehyde detection. Issue 38 (24th September 2020) - Han, Zejun; Qi, Yuan; Yang, Zhengyi; Han, Hecheng; Jiang, Yanyan; Du, Wenjing; Zhang, Xue; Zhang, Jizhi; Dai, Zhengfei; Wu, Lili; Fletcher, Cameron; Wang, Zhou; et al.
Abstract : The sensing mechanisms and effective strategies for enhancing the formaldehyde detection performance of metal oxide semiconductors have been reviewed. Abstract : Formaldehyde is widely used in chemical production, wood fixatives, petroleum production and other industrial processes. However, the adverse issues caused by formaldehyde have in recent years been attracting increasingly greater attention. It has been reported that indoor formaldehyde pollution can lead to mucosal inflammation, pulmonary edema, nausea, vomiting, leukemia, pregnancy syndrome and other diseases. Consequently, this has inspired large research efforts into improving the techniques by which low concentration formaldehyde can be detected and degraded. As such, it is critical to develop improved sensors for public use with remarkable sensitivity and selectivity for the detection of formaldehyde. Metal oxide semiconductor gas sensors represent the most efficient and portable detection systems for indoor use due to the merits of low cost, easy operation, high sensitivity and quick response. In this review article, we first introduce the fundamental mechanisms by which metal oxide semiconductor sensors can detect formaldehyde, followed by a summary of the current state-of-the-art research progress on sensing materials. Thereafter, strategies for enhancing the sensing performance and selectivity of metal oxide semiconducting materials towards formaldehyde are discussed. Finally, based on this analysis of the recent research progress, we provide perspectives for future development in this field.